Perancangan Ulang Logo dan Media Promosi Proko Coffee untuk Meningkatkan Identitas Merek - Clarence Aggamitto; Hendi Thamrin (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2024)
The coffee shop population continuing to grow in Indonesia, competition is becoming increasingly fierce in creating coffee shop brands, coffee shop business owners will increasingly compete for customers in order to survive amidst the proliferation of coffee shops, especially in the Tangerang area. The presence of a visual identity can be the key for a brand to create a significant impact, including in terms of differentiating itself and providing uniqueness compared to its competitors. Proko Coffee is a coffee shop that was founded in 2020, precisely June 1 2020 and was founded by Maredo Gustam. This coffee shop located in Tangerang does not yet have a visual identity that is identified and well presented, especially in the logo and promotional media, and does not yet have brand guidelines. consistent. So, with this final assignment the aim is to redesign the Proko Coffee logo and promotional media to strengthen the brand identity so that it can develop amidst the rapid growth of coffee shops in Indonesia. Based on this problem, the author redesigned the logo and promotional media owned by Proko Coffee Shop from Tangerang using a qualitative approach, namely by distributing a survey questionnaire containing several questions regarding the visual identity and logo of Proko Coffee to people who spend a lot of time in coffee shops. as well as directly interviewing related parties. As a result, this final project uses Graphic Standard Manual (GSM) which will be applied to supporting media properly and consistently.